2009
DOI: 10.1111/j.1460-2695.2009.01383.x
|View full text |Cite
|
Sign up to set email alerts
|

Residual stress and constraint effects on cleavage fracture in the transition temperature regime

Abstract: A B S T R A C T Defects in structural components are often associated with welds that may contain significant levels of residual stress. Whilst the primary load acting on the component may induce low constraint conditions at the crack tip, the presence of residual stresses, e.g. due to welding, can modify this constraint level and consequently influence the observed fracture toughness behaviour. This paper presents the results of a combined experimental and numerical programme aimed at exploring this issue. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…The effect of constraint on cleavage fracture toughness was discussed by Beardsmore 10 , who suggested that the presence of a residual stress field of the magnitude and distribution produced in these samples should result in a higher level of constraint, such that the failure condition is actually reached at a lower value of J than in an unstrained sample. This is in agreement with the constraint calculations of Lee et al 15 . who calculated a higher (positive) T ‐ and Q ‐stress for PCT specimens when compared with CT specimens.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The effect of constraint on cleavage fracture toughness was discussed by Beardsmore 10 , who suggested that the presence of a residual stress field of the magnitude and distribution produced in these samples should result in a higher level of constraint, such that the failure condition is actually reached at a lower value of J than in an unstrained sample. This is in agreement with the constraint calculations of Lee et al 15 . who calculated a higher (positive) T ‐ and Q ‐stress for PCT specimens when compared with CT specimens.…”
Section: Discussionsupporting
confidence: 92%
“…The K Jc values at failure were calculated (i) according to the ASTM procedure, based on the area under the primary load versus crack mouth opening displacement record from each test 8 and (ii) using the JEDI procedure to determine J inclusive of any residual stress fields 15 . In each case the value of J at cleavage was converted to an equivalent K Jc using the standard plane strain formulation: where E is Young's modulus, ν is Poisson's ratio and J c is the derived value of J at cleavage.…”
Section: Methodsmentioning
confidence: 99%
“…8, can be used to calculate the residual stress triaxiality (ratio of hydrostatic to von Mises stresses) at any location along the measurement line. This parameter can have a significant effect on crack initiation and opening behaviour in ductile materials [34] and on fracture [35][36][37]. The measurements show that exceptionally high stress triaxiality is present (approaching unity) in the region between 17 and 22 mm from the CT blank front face.…”
Section: Discussionmentioning
confidence: 86%
“…Because the heat treatments used for these samples will not necessarily be the same as those used in other published tests on JRQ and JFL, these particular materials are identified as JRQ (BSL) and JFL (BSL). An A533B Class 1 plate heat treated such that the mean fracture toughness at room temperature would be ∼100 MPa√m (UM). Fracture toughness measurements and fractography were carried out on both standard and previously compressed compact tension samples., 19 This present report uses data from the standard samples only.…”
Section: Investigation Of Modelsmentioning
confidence: 99%
“…An A533B Class 1 plate heat treated such that the mean fracture toughness at room temperature would be ∼100 MPa√m (UM). Fracture toughness measurements and fractography were carried out on both standard and previously compressed compact tension samples., 19 This present report uses data from the standard samples only.…”
Section: Investigation Of Modelsmentioning
confidence: 99%